Penggunaan Penerangan Jalan Umum Berbasis Tenaga Surya - Wartoyo, Bayu Purbo; Suhanto, Suhanto; Driyono, Bambang (LPPM Universitas Bumigora, 2024)
The world's energy sources have undergone several changes, from initially the majority used biomass to fossils which were triggered by the industrial revolution in the 1900s. The higher use of fossil energy causes an increase in greenhouse gas emissions. One alternative that can be done is the use of solar power plants. An example of its use is in fulfilling electrical energy as lighting with the use of electrical energy which still uses small power. Makassar Aviation Polytechnic together with Airnav Indonesia, collaborates in terms of utilizing solar-based renewable energy implemented in Mapanget Village, North Sulawesi. As for some points in this location, there is still minimal lighting so that it is prone to accidents and crime. The method used in this community service activity is the provision of knowledge about solar cells, solar cell wiring diagrams, and how to check and repair solar-based public street lighting. The results obtained from this community service are that people understand, can install and repair solar cell-based public street lighting. In conclusion, the existence of public street lighting on some roads in Mapanget Village can reduce the accident rate and provide a sense of security for the community when crossing the road